A dance of lies - Arena, Brittney (Del Rey, 2025)
"In this lyrical romantic fantasy, a disabled dancer framed for murder is thrust into a lethal feud between royals where she must use her wits and artistry to earn her freedom, even as her ploys land her in the centre of a dangerous political web that risks both her life and her heart. After spending two years in prison for a murder she didn't commit, Vasalie Mora - the former King's Jewel, renowned for her dancing - is offered a chance at freedom by the same man who framed her: King Illian of East Miridran. If she agrees to act as his spy at the upcoming Gathering, where powerful royal families converge to discuss political alliances, Illian promises to clear her name. And with no other choice, Vasalie accepts the deal. But returning to her former glory proves impossible when Vasalie realizes her body has not endured her time in prison as well as anyone had hoped. Still determined to earn her freedom, Vasalie throws herself into the underbelly of the Gathering disguised as a dancer, uncovering political secrets and plots that could undermine the whole of the North. But as the web of betrayal and lies spreads between kingdoms, Vasalie will find herself caught in affairs that risk more than just her own life, and if she wants to escape the reach of King Illian, it may mean jeopardizing the lives of her new friends and her freedom - along with the tantalizing relationship brewing between her and a man she absolutely cannot be caught falling for." -- Provided by publisher.